Guidelines for neuromuscular ultrasound training. Issue 4 (12th August 2019) - Tawfik, Eman A.; Cartwright, Michael S.; Grimm, Alexander; Boon, Andrea J.; Kerasnoudis, Antonios; Preston, David C.; Wilder‐Smith, Einar; Axer, Hubertus; Hobson‐Webb, Lisa D.; van Alfen, Nens; Crump, Nicholas; Shahrizaila, Nortina; et al.
Abstract: Neuromuscular ultrasound has become an essential tool in the diagnostic evaluation of various neuromuscular disorders, and, as such, there is growing interest in neuromuscular ultrasound training. Effective training is critical in mastering this modality. Our aim was to develop consensus‐based guidelines for neuromuscular ultrasound training courses. A total of 18 experts participated. Expert opinion was sought through the Delphi method using 4 consecutive electronic surveys. A high degree of consensus was achieved with regard to the general structure of neuromuscular ultrasound training; the categorization of training into basic, intermediate, and advanced levels; the learning objectives; and the curriculum for each level. In this study, a group of neuromuscular ultrasound experts established consensus‐based guidelines for neuromuscular ultrasound training. These guidelines can be used in the development of the specialty and the standardization of neuromuscular ultrasound training courses and workshops.